MULTIPLE XYLITOL DEHYDROGENASE SYSTEM OF ASPERGILLUS ORYZAE - Ha, Tran Lien (Vietnam Journal of Science and Technology, 2012)
Aspergillus oryzae P5 has some xylanolytic enzymes such as xylanase of 8.8 U/mg, a-L arabinofuranosidase of 1.2 U/mg, b- xylosidase of 1.9 U/mg and xylose reductase activities were 11.3 U/mg and 13.4 U/mg by using NADH and NADPH. However, xylitol dehydrogenase activities were 5.5 U/mg and 1.8 U/mg using NAD+ and NADP+ as cofactor, respectively. In genome of A. oryzae, there are 4 fragments, which are homologous with DNA xylitol dehydrogenase genes of other strains. Based on DNA sequences of these fragments, 2 genes were cloned. One of them (xdhA) gene encodes for NAD+-dependent xylitol dehydrogenase activity. The gene was knock out in A. oryzae P5, however the mutant still showed NAD+-dependent xylitol dehydrogenase activity. Therefore, A. oryzae P5 has multiple xylitol dehydrogenases.